The Byzantine Empire (?) between denialism and resilience: the draft of a disfigured history - Dias, João Vicente de Medeiros Publio (Romanitas - Revista de Estudos Grecolatinos, 2026)
This article proposes an exploratory study of the traditional separation between Roman History and Byzantine History, arguing that the Byzantine Empire should be understood as a transformed continuation of the Roman Empire rather than as a distinct entity. Based on an extensive bibliographical review and historiographical analysis, the article discusses how the use of the term “Byzantine” is linked to a persistent denial of the Eastern Romans’ claim to the Roman legacy, resulting from political, religious, and cultural disputes within the context of Latin Christendom and the West. By examining key historical moments, the text questions the validity of these traditional chronological milestones as points of rupture. Instead, it highlights the institutional, cultural, and identity continuity that the Eastern Romans (rhomaioi) themselves recognized in their own society. Such continuity was only possible through transformations and adaptations to new historical circumstances. By emphasizing the Empire’s resilience in the face of these changes, the article exposes historiographical prejudices rooted in Enlightenment thought and proposes a more integrated and dynamic perspective on the long durée of Late Antique and medieval Romanity.
Keywords: Roman Empire; Byzantine Empire; Late Antiquity; Denialism; Resilience